2017
DOI: 10.1007/s10265-017-0924-6
|View full text |Cite
|
Sign up to set email alerts
|

CKB1 is involved in abscisic acid and gibberellic acid signaling to regulate stress responses in Arabidopsis thaliana

Abstract: Casein kinase II (CK2), an evolutionarily well-conserved Ser/Thr kinase, plays critical roles in all higher organisms including plants. CKB1 is a regulatory subunit beta of CK2. In this study, homozygous T-DNA mutants (ckb1-1 and ckb1-2) and over-expression plants (35S:CKB1-1, 35S:CKB1-2) of Arabidopsis thaliana were studied to understand the role of CKB1 in abiotic stress and gibberellic acid (GA) signaling. Histochemical staining showed that although CKB1 was expressed in all organs, it had a relatively high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Recent molecular genetics and biochemical analyses suggest that CK2 is involved in ABA signaling and abiotic stress responses (for review: Vilela et al 2015b). So far, studies of CK2 knockout mutants and RNAi lines suggest that CK2αs and CK2β1 are positive regulators of ABA responses (Mulekar et al 2012; Mulekar and Huq 2014; Wang et al 2014; Yuan et al 2017), whereas biochemical studies suggest that CK2 negatively regulates SnRK2-mediated ABA signaling (Vilela et al 2015a). It is thus controversial whether casein kinase II subunits (CK2s) positively or negatively regulate ABA signaling in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular genetics and biochemical analyses suggest that CK2 is involved in ABA signaling and abiotic stress responses (for review: Vilela et al 2015b). So far, studies of CK2 knockout mutants and RNAi lines suggest that CK2αs and CK2β1 are positive regulators of ABA responses (Mulekar et al 2012; Mulekar and Huq 2014; Wang et al 2014; Yuan et al 2017), whereas biochemical studies suggest that CK2 negatively regulates SnRK2-mediated ABA signaling (Vilela et al 2015a). It is thus controversial whether casein kinase II subunits (CK2s) positively or negatively regulate ABA signaling in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellin and ABA are known to antagonistically regulate various developmental processes throughout the plant life cycle, including stress responses ( Yuan et al, 2017 ), seed germination and seedling growth ( Lin et al, 2015 ; Zhong et al, 2015 ; Liu et al, 2016 ), and the formation of arbuscular mycorrhizal symbiosis ( Martín-Rodríguez et al, 2016 ). For example, in rose ( R. hybrida ), the activity of Rh-PIP2;1 , which is involved in ethylene-mediated rose petal expansion, was reported to be enhanced by GA 3 at the later stages but suppressed by ABA during the early stages ( Ma et al, 2008 ; Li et al, 2009 ; Pei et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CKB1 under various stresses was analysed in our previous study (Yuan et al . ), which showed that exogenous ABA induced a rapid increase of CKB1 expression in 1 h. However, exogenous GA induced a gradual increase of CKB 1 over 8 h. For response to cold stress, expression of CKB1 was reduced under low temperatures. For response to osmotic stress, the expression of CKB1 first decreased and then increased with time when treated with mannitol.…”
Section: Discussionmentioning
confidence: 99%
“…The CKB1 gene over‐expression lines (CKB1‐OE) were generated by our lab and were described in a previous study (Yuan et al . ). Briefly, cDNA of Col‐0 was used as template to amplify fragments of the CKB1 gene with PCR.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation